THE Impact of Disruption on the Relationship Between Exploitation, Exploration, and Organizational Adaptation - Xiao, Yao; Cen, Jie; Soberg, Peder (Frontiers in Sociology, 2021)
Firms should deploy exploration and exploitation to foster organizational adaptation. Previous research on exploration and exploitation lacked a focus on disruption implications in different contexts. This study aims to empirically test a moderation model including disruption events, exploration, exploitation, and organizational adaptation and enable a deeper understanding of organizational learning and innovation theory to yield competitive advantage and sustainability of innovative firms. Our results reveal that exploration is more effective during outside disruption events. The results do not support the concept that exploitation is more effective during inside disruptions. Disruptions also moderate the combined effect of exploration and exploitation. Although they are generally complementary in facilitating organizational adaptation, a singular focus on either exploration or exploitation is as effective as is combining exploration and exploitation during inside and outside disruption events. The results of an event study using seven Chinese international firms, including Alibaba, Meituan, Dianping, Baidu, Beibei, TP-link, and Maxio, provided 132 completed and usable questionnaires that supported our hypotheses. Our study contributes to a better understanding of disruption, exploration, exploitation, and related performance implications.